(untitled) (Journal of the College of Basic Education, 2022)
The research deals with the role of the English military forces in protecting the coastal cities of the United Provinces, which later became known as (Netherlands), and the latter’s submission to the decisions of the Kings of England and the exploitation of their military assistance, due to the need of the United Provinces to protect from the invasions of the Spaniards and their constant threat to its lands, and thus the English role in Holland was characterized The two sides are political and military, and obligating the Dutch to pay the dues of the English the military protection to their areas, at the same time England was encouraging from time to time military conflicts within those united provinces to make them weak and in constant need of English support.